Keterkaitan Spasial Antarwilayah Berdasarkan Potensi Ekonomi - La Ode Abdul Rasyid Halidun; Ihsan Ihsan; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Regional cooperation in Mamminasata area has not had a significant impact on equitable development in Makassar City, Maros Regency, Gowa Regency and Takalar Regency. Inequality of development results in debilitating regional linkages. The purpose of this study is to know the economic potential and to find out the spatial linkages between regions in Makassar City, Gowa Regency, Maros Regency, and Takalar Regency. This study used secondary data with quantitative and qualitative approaches. The methods used, which cover location quotient, growth ratio models, shift share, global moran’s, LISA, and descriptive. The results of this study indicate that there are 8 economic sectors included in the regional development priorities, which cover the agricultural sector, mining and quarrying sector, processing industry sector, electric, gas and water supply sector, building sector, transportation and communication sector, finance sector, and services sector. Based on the results of the autocorrelation spatial analysis, only the processing industry sector has significant spatial linkages and form a cluster pattern of High-High value (Hot Spot) in Makassar City and Gowa Regency. Finally, that the processing industry sector can be used as focus on the development to increase spatial linkage in the region Mamminasata.